Information society statistics and indicators: The case of Turkey - Atici, Buenyamin (Academic Journals, 2010)
This study, performed through the basic structures of information society, refers to the global dimensions of change by knowledge economy and information society as statistics which have different indicators to help us determine the position of Turkey on this change. In order to understand the position of Turkey on information society, several indexes were researched. In this study, the level of Turkey as an information society is stated through the digital opportunity, ICT/OI, e-readiness, networked readiness and digital access indexes.
Keywords: Information society; knowledge economy; information and communication technologies; index